Protocolo de PCR para la detección de Brucella melitensis y REV-1 - Alvarez, Lucia Paula; Robles, Carlos Alejandro (EEA Bariloche, 2020)
Primers utilizados: REV Fw 5’ CAG GCA AAC CCT CAG AAG C 3’ REV Rv 5’ GAT GTG GTA ACG CAC ACC AA 3’ Amplifican un de 218 pb en REV-1. Cita: Garcia-Yoldi, D., et al., Multiplex PCR assay for the identification and differentiation of all Brucella species and the vaccine strains Brucella abortus S19 and RB51 and Brucella melitensis Rev1. Clin Chem, 2006. 52(4): p. 779-81.